Pengaruh Gaya Belajar Terhadap Kemampuan Penalaran Matematis Siswa SD 5 Mejobo - Kavita Hataru Cipta Rizky; Nikmatu Tasya; Hemalia Hemalia; Fitriyah Amaliyah (Politeknik Kampar, 2024)
This research aims to examine the influence of learning styles on students' mathematical reasoning abilities at SDN 5 Mejobo. The learning styles studied include three main categories, namely auditory, kinesthetic and visual. Mathematical reasoning abilities are measured through tests that cover various aspects of reasoning such as identifying patterns, making generalizations, and solving mathematical problems logistically. This research uses quantitative methods with a survey approach. The research population was all 6th grade students at SDN 5 Mejobo, totaling 12 students, and the entire population was used as a sample population using saturated sampling techniques. Data was collected through a learning style questionnaire adapted from the VARK model and a mathematical reasoning test that refers to NCTM standards. Data analysis was carried out using regression and correlation analysis techniques with the help of SPSS software. The research results show that learning style does not have a significant influence on students' mathematical reasoning abilities (value 0.030 > 0.05). These findings indicate that individuals' learning style preferences do not determine their mathematical reasoning abilities. Therefore, it is recommended that other factors such as teaching methods, learning motivation, and learning environment be considered in an effort to strengthen students' mathematical reasoning abilities. It is hoped that this research will provide insight into the development of learning strategies that are more efficient and meet student needs.